Perlindungan Hukum Bagi Korban Tindak Pidana Lingkungan Hidup Oleh Korporasi - Fikri Ananta Nur Rasyid; Asnah; Aullia Vivi Yulianingrum (Jurnal Ilmu Pendidikan dan Sosial, 2023)
In environmental crimes, if a corporation has been sentenced to a criminal sentence, it is as if the sentence has been fulfilled. Considering that environmental crimes can result in many victims, both physically and psychologically, who feel disadvantaged as a result of criminal acts committed by corporations. However, along with the number of environmental crime cases, there are also many rights of social victims and social objects that have not been fulfilled. Therefore, this research wants to find the ideal legal protection for victims of environmental crimes. This research method uses a qualitative type of literature review. Primary data source UUD RI and research journals. This data analysis uses content content. The results of the study show that the main form of legal protection for victims of environmental crimes besides the form of Corporate Social Responsibility (CSR) is environmental restoration for the benefit of environmental preservation. In resolving environmental disputes, the parties can use out-of-court channels, namely mediation or court channels with the concept of restorative justice that emphasizes the rights of victims and the interests of perpetrators of environmental crimes.